Relationship of Tree Architecture on Canopy Throughfall and Stem Flow in The Upstream of Batang Mahat River Basin Lima Puluh Kota Regency Indonesia - Reni Ekawaty; Yonariza Yonariza; Eri Gas Ekaputra; Ardinis Arbain; Rusnam Rusnam (Journal of Applied Agricultural Science and Technology, 2023)
A study about the effect of tree architecture on canopy throughfall and stem flow was conducted upstream of Batang Mahat River Basin, Lima Puluh Kota Regency, West Sumatra, Indonesia. Four dominant tree species in the location, Voacanga foetida, Guioa sp, Schima wallichii and Rhodoleia champonii, were selected and represented in architecture by Scarrone, Schoute, Rauh and Leeuwenberg, respectively. Furthermore, the sample was three trees of each species. The throughfall canopy was measured using a 1 x 1 m plastic plot placed at the edge, while the stem flow was calculated by two meters plastic tube with a five-litre tank at the bottom. These data were collected eight times over one month. The study aimed to the analyzed relationship between tree architecture and canopy throughfall and stem flow upstream of the Batang Mahat River Basin. The result showed that Schima wallichii differed significantly in throughfall canopy relative to the other three species. Additionally, V. foetida significantly differed in stem flow compared to the other tree species. There was no correlation between throughfall canopy, stem flow and precipitation, but the two parameters were affected by three architectures. These findings are useful for soil and water conservation in the upper Mahat River Basin.